Penerapan Asesmen Diagnostik Kognitif Pada Kurikulum Merdeka Di SMP Islam Al-Fadhila Demak - Aulia, Egi Dina (Proceedings Series of Educational Studies, 2025)
The objective of this study is to examine the stages of implementing cognitive diagnostic assessments, to investigate the factors that hinder the implementation of cognitive diagnostic assessments, and to identify the strategies that can be taken so the implementation of cognitive diagnostic assessments in the independent curriculum can be maximized. The research method used in this research is a qualitative approach. Data collection techniques are observation, interviews, and documentation. This research was conducted at Al-Fadhila Demak Islamic Junior High School. The implementation of diagnostic assessments consists of the design stage, the implementation of assessments, and diagnosing the level of understanding of students. Some of the obstacles experienced are the very high load of duties and responsibilities, the large number of students in each class, and educators who do not have a reflective attitude (the lack of motivation of educators to question the quality and effectiveness of the assessments carried out).